The effect of additive biomaterials on the printability and characterization of PCL-based composite scaffolds fabricated by screw extrusion 3D printing - Lan Xuan Phung; Bang Thi Le; Phuong Mai Thi Nguyen; Huyen Trang Thi Nguyen; Trung Kien Nguyen (Materials Research Express)
To enhance cell adhesion and cell interactions for diverse tissue engineering applications, polycaprolactone (PCL) has been integrated with few biomaterials such as ceramic (i.e. tricalcium phosphate - TCP), hydrogel (i.e. sodium alginate - SA), and synthetic polymer materials (i.e. polyethylene glycol - PEG). Each type of additive material presents typical characteristics, the comparison among these three biomaterial types is currently inadequate. In this study, a 3D printer using direct powder screw extrusion technique was applied for fabricating three types of PCL-based composite scaffolds (namely, PCL-PEG, PCL-SA, and PCL-TCP) which are representative of each type of additive material. The experimental evaluation on the printability, scaffold morphology, surface roughness, hydrophobicity, and cell proliferation of these PCL-based composite scaffolds were compared under the same conditions. The results demonstrated that the additive materials with an amount from 20 wt% have a notable effect on the printability of PCL matrix material and significant enhancement of cell proliferation. The incorporation of PEG with PCL is the most effective choice to increase the hydrophilicity of the scaffold surface. The PCL-SA scaffold provided a more favorable environment for cells at the initial stage, whereas the PCL-TCP scaffold demonstrated superior cell proliferation over time. These findings also demonstrate the feasibility of a direct powder screw extrusion printhead on 3D printing for composite scaffolds in tissue engineering applications.